Antimicrobial Activity of Some Algal Species Belonging to Cyanobacteria and Chlorophyta - Demiriz, Tugba; Cokmus, Cumhur; Pabuccu, Koksal (Asian Journal of Chemistry, 2010)
In this study, antimicrobial activity of five algal species (Oscillatoria limosa, O. limnetica, Phormidium tenue, Chlorella vulgaris, Spirulina major) which were grown in proper culture condition was searched with their extracts that obtain by using different solvent (methanol, ethanol, n-butanol, acetone, hexane, 0.5 M tris-HCl pH 8.00). The antimicrobial activity of algal extracts were tested on Staphylococcus aureus ATCC 19213, Bacillus subtilis ATCC 6633, Salmonella enteretidis ATCC 13076 and Escherichia coli O157:H7 by using disc diffusion method. Among the investigated algae, Spirulina major has had the highest antimicrobial activity. Buffer extracts of this algal species (0.5 M tris- HCl, pH: 8,0) was found to be effective on S. aureus ATCC 19213, B. subtilis ATCC 6633, S. enteretidis ATCC 13076 and E. coli O157:H7. S. aureus ATCC 19213 and E.coli O157:H7 were the most sensitive species; B. subtilis ATCC 6633 was the most resistant bacterial strains against to antimicrobial activity of the algae extracts.